The effects of midsole bending stiffness on ball speed during maximum effort soccer kicks - Cigoja, S.; Vienneau, J.; Nigg, S. R.; Nigg, B. M. (Footwear Science, 2019)
The soccer kick is the most prominent movement in soccer. Kicking performance depends on two major factors: kicking accuracy and ball speed. During the soccer kick, momentum is transferred from the foot/cleat to the ball. This interplay between the foot/cleat and the ball can be modelled as a mixture of `impulse-like` and `throwing-like` components. While kicking the ball, the metatarsophalangeal (MTP) joint and the cleat experience deformation. This deformation can be reduced by increasing the bending stiffness of the cleat`s midsole. Therefore, the purpose of this study was to investigate experimentally the influence of midsole bending stiffness on ball speed during maximum effort soccer kicks. Twenty male subjects (mean ± SD; age: 29.5 ± 5.6 years, height: 175.5 ± 6.4 cm, mass: 74.3 ± 8.4 kg) performed six maximum effort soccer kicks in five stiffness conditions. Kinematic data were collected using an optical motion capture system consisting of eight high-speed cameras, and ball speed was recorded using a radar gun. There was no significant difference in the average ball speed between the five stiffness conditions when all subjects were pooled. Further, there was no significant difference in the change of the MTP joint angle from before ball contact to after ball contact between the stiffness configurations. Thirteen (of the 20) subjects showed the highest ball speed in the two stiffest cleats. The differences between the best and the worst performing stiffness configurations across all subjects ranged from 2.2 km/h to 9.2 km/h. The optimal stiffness condition that resulted in highest ball speed was subject specific, and therefore soccer cleats need to be tuned to individual players.